(untitled) (The Peerian Journal, 2025)
This article explores the linguistic and cultural aspects of holiday and game names in English and Uzbek. It examines their etymology, semantic structures, and sociocultural significance. By analyzing similarities and differences in naming conventions, the study highlights how traditions and cultural values are reflected in language. Additionally, the research delves into how globalization has influenced the borrowing and adaptation of certain holiday and game names in both languages.